Civil Engineering structure and Bioengineering Technique for landslide reduction and there cost comparison; with reference to study in Kageshwori Manohara Municipality of Kathmandu, Nepal (Universal Technical Journal of Lumbini International Academy of Science and Technology, 2025)
Landslides pose a significant threat to communities in hilly and mountainous regions of Nepal where steep terrain and heavy monsoon rainfall contributes to their occurrence. This study focused on the study of four landslide sites for case analysis. Comprehensive data collection included Slope length, Slope width, Slope Angle, Material Drainage, Aspect, Site Moisture, Type of Soil, Type of Erosion/Mass Movement, past history of Landslide. Based on this data and suggestion from the expert, various bioengineering and civil engineering techniques were proposed for soil stabilization and erosion control. Bioengineering measures such as grass seeding, shrub and tree plantation, brush layering, jute netting, along with civil engineering methods like riprap, gabion work, soil nailing, shotcrete, chutes, and drains are suggested. The study also included a cost comparison between bioengineering and civil engineering measures. The cost analysis revealed that the expenditure for bioengineering measures amounted to NRs. 3,202,854.52, while civil engineering works incurred NRs. 6,199,496.55. Typically, the cost ratio between vi bioengineering and civil engineering is expected to be 1:3. However, due to the inclusion of water management components like stream chutes and riprap in bioengineering, the observed ratio is closer to 1:1.94.In conclusion, this research highlights the significance of adopting bioengineering techniques as a sustainable, cost effective and community-centered approach to landslide risk reduction. The outcomes of this case study offers a holistic framework for mitigating landslide hazards in vulnerable areas like Adhikari Tole, ultimately contributing to the safety and well-being of its residents. The approach adopted in this study can serve as a model for similar landslide-prone regions in Nepal and other countries facing similar challenges.